The Importance of Students’ Perception of Online Learning During Pandemic - Fivy Andries; Fergina Lengkoan (AIBPM Publisher, 2023)
The pandemic of COVID-19 has the impact to the Indonesian government through its Ministry of Education and Culture, wherefrom classroom to online classroom. This study is a collective case study consisting of analysis survey on students’ perceptions of online learning during the COVID-19 pandemic. 83 students of English Education Department at Universitas Negeri Manado. Their perceptions of their online classroom that will be recorded through a survey. The perceptions are in terms of students’ participation, accessibility, material and assignment delivery, and the use of application in online learning. The results summarized into tables and narrative descriptions. This study identified three major struggles in conducting online learning the result almost a half of them not given positive perception of online learning. Although more than a half the students stated they have trouble with online learning process, such as the bad signals, bored, can’t meet friends, they are not focused on leaning, they don’t understand the material, and they location was not supported for their activity in online learning because they lived in the place like village and hinterland. This study may be able to assist in further related research and become the basis for consideration for the progress and sustainability of the teaching and learning process in the future without harming students, teachers, and also parents.